Genomic in situ hybridization (GISH) and performance analysis in intergeneric hybrids from five consecutive generations of Erianthus x Saccharum - V.P. Sobhakumari; K. Mohanraj (Caryologia)
Erianthus arundinaceus, one of the species of ‘Saccharum complex’ has a number of important agronomic traits including good ratooning ability, tolerance to both drought and waterlogging, disease resistance and vigor and is of interest as a potential source of parental germplasm to sugarcane breeders. We report here for the first time the chromosome composition, Erianthus chromosome transmission patten and agronomical trait evaluation of Erianthus addition lines in five consecutive generations of E. arundinaceus x Saccharum. The hybridity of randomly selected clones could confirm with Erianthus Specific Tandem Repeat (ESTR) sequences. The results of classical cytology revealed that the mode of transmission of gametes, except in the second generation, followed n+n pattern whereas in second generation (CYM 07-971) it was showing 2n+n with elimination of few chromosomes. Progressive elimination of Erianthus chromosomes is observed in consecutive generations where the F1 showed 30 Erianthus chromosomes and it was ranged from 0-2 in fifth generation. Agronomical trait analysis indicates that further backcrossing with commercial clones with high juice quality or intercrossing among the selected progenies would improve both juice quality and cane traits in E. arundinaceus x Saccharum hybrids.